Avaliação de técnica cirúrgica parendodôntica: apicectomia em 90 graus, retrocavitação com ultra-som e retrobturação com MTA - Daniel Pozza (2005)
The Dentistry technological innovations have been modifying the endodontics surgery paradigms. The most conventional techniques, as apical resection for drill in 45° angle, and retrocavitation with spherical steel drill and root-end filling with amalgam, are being gradually substituted for new sequences of procedures that aim to increase the surgical benefits, improving the clinical prognostic. The methodology applied in this paper is based on literature review and laboratorial research. The results shows a number of advantages in using procedures as the resection in 90 degrees, ultrasonic preparation of root-end cavities and root-end filling with Mineral Trioxide Aggregate (MTA) in the endodontics surgeries.